Transport in biological media - Becker, Sid; Kuznetsov, Andrey V. (Elsevier/Academic Press, 2013)
Transport in Biological Media is a solid resource of mathematical models for researchers across a broad range of scientific and engineering problems such as the effects of drug delivery, chemotherapy, or insulin intake to interpret transport experiments in areas of cutting edge biological research. A wide range of emerging theoretical and experimental mathematical methodologies are offered by biological topic to appeal to individual researchers to assist them in solving problems in their specific area of research. Researchers in biology, biophysics, biomathematics, chemistry, engineers and clinical fields specific to transport modeling will find this resource indispensible. Provides detailed mathematical model development to interpret experiments and provides current modeling practices Provides a wide range of biological and clinical applicationsIncludes physiological descriptions of models.